Wear behavior of an Al2O3/TiC/TiN micro-nano-composite ceramic cutting tool in high-speed turning of ultra-high-strength steel 300 M. Issue 9 (December 2016) - Wang, Dong; Zhao, Jun; Cao, Yan; Xue, Chao; Bai, Yu
Abstract An Al2 O3 -based micro-nano-composite ceramic tool material reinforced with TiN micro-particles and TiC nanoparticles was fabricated by using the hot-pressing technique. The wear behavior of the Al2 O3 /TiC/TiN micro-nano-composite ceramic cutting tool (AT10N20) in high-speed turning of ultra-high-strength steel 300 M was investigated by comparison with the commercial Al2 O3 /TiC composite ceramic tool CC650. Worn and fractured surfaces of ceramic cutting tools were observed and analyzed via the scanning electron microscopy (SEM) combined with the energy-dispersive X-ray spectroscopy (EDS). The results showed that the main wear modes of AT10N20 and CC650 were flank wear and rake wear. The crater on the rake face of AT10N20 initially occurred at cutting speed of 400 m/min, while it occurred at cutting speed of 200 m/min for CC650. In addition, the rake wear and flank wear became more severe when the cutting speed attained 400 m/min. The cutting speeds higher than 400 m/min were unfavorable for turning of ultra-high-strength steel 300 M. Wear mechanisms of AT10N20 and CC650 in high-speed turning of the ultra-high-strength steel were abrasion and adhesion.